An Analysis of Financial Distress in Village-Owned Enterprises (BUM Desa) in Gorontalo Regency - Djou, Nurmat; Abdullah, Julie; Junus, Onong; Saprudin, Saprudin (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the financial distress conditions of Village-Owned Enterprises (BUM Desa) in Gorontalo Regency. This research uses a quantitative approach with descriptive data analysis techniques using the Springate S-Score model. Data collection was conducted through documentation methods, including stages such as collecting financial reports, performing financial ratio analyses, conducting financial distress analysis, and drawing research conclusions. The financial report data analyzed spans five years (2019–2023), constituting a time-series dataset. The results of the study indicate that, in general, BUM Desa in Gorontalo Regency are not experiencing financial distress. Of the six BUM Desa analyzed, three consistently demonstrated sound financial health over the five-year period, two exhibited fluctuations in financial performance but overall remained within the healthy category, and only one showed a low Springate score. However, this score was not sufficient to classify the enterprise as significantly distressed, as it continued to demonstrate ongoing business activities and adequate liquidity. Thus, it can be concluded that, overall, BUM Desa in Gorontalo Regency are in a financially healthy condition.